Clinical outcomes of minimally invasive endoscopic and conventional sternotomy approaches for atrial septal defect repair - Chu, Michael W.A. (Canadian Medical Association, 2014)
BACKGROUND: Concerns remain that minimally invasive atrial septal defect (ASD) repair may compromise patient outcomes. We compared clinical outcomes of adult patients undergoing ASD repair via a minimally invasive endoscopic approach versus a “gold standard” sternotomy. METHODS: We retrospectively reviewed the clinical outcomes of consecutive patients who underwent ASD patch repair at our institution between 2002 and 2012. We compared in-hospital/30-day mortality, postoperative complications, length of stay in hospital and in the intensive care unit and blood product requirements between patients who underwent right mini-thoracotomy (MT) and those who underwent conventional sternotomy. RESULTS: During the study period, 73 consecutive patients underwent ASD patch repair at our institution: 51 (age 47 ± 16 yr, 66.7% women) in the MT group and 22 (age 46 ± 21 yr, 59.1% women) in the sternotomy group. In-hospital mortality was similar between the 2 groups (MT 0% v. sternotomy 4.5%, p = 0.30). There were no significant differences in any postoperative complications or blood product requirements. No patients in the MT group suffered stroke, retrograde aortic dissection or leg ischemia. Mean intensive care unit (MT 1.2 ± 1.2 d v. sternotomy 1.7 ± 2.2 d, p = 0.26) and hospital length of stays (MT 5.1 ± 2.2 d v. sternotomy 6.3 ± 3.6 d, p = 0.17) were similar between the groups; however, there was a trend toward fewer patients requiring prolonged hospital stays (> 10 d) in the MT group (3.9% v. 18.2%, p = 0.06). CONCLUSION: Repair of ostium secundum and sinus venosus ASD can be performed safely via MT endoscopic approach with similar outcomes as sternotomy. Patient preference for a more cosmetically appealing incision may be considered without concern of compromised outcomes.